2005
DOI: 10.1590/s0101-31572005000200009
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura de propriedade e de controle das empresas de capital aberto no Brasil

Abstract: Ownership and Control in Brazilian Limited Liability Companies. Abstract: This paper has as its main objective to measure the magnitude of deviations between control rights and cash-flow rights for the ultimate shareholder with the largest voting rights of limited liability companies in Brazil. Furthermore, it pinpoints how these discrepancies are generated, evaluating the relative importance of the issuance of preferred stocks with no voting rights, pyramidal arrangements of ownership, and cross-shareholdings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
14

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 10 publications
1
13
0
14
Order By: Relevance
“…There are descriptive studies that have reported on the extreme degree of ownership concentration that prevailed until recently (Aldrighi & Mazzer, 2005, 2007Leal, Carvalhal-da-Silva, & Valadares, 2002;among others) and the decline in the degree of ownership concentration in Brazilian companies in recent years (Canellas & Leal, 2009;Gorga, 2009;Sternberg, Leal, & Bortolon, 2011), while others have linked ownership structure to performance or market value of a company (Leal & Bortolon, 2009;Leal & Carvalhal-da-Silva, 2006;Okimura, Silveira, & Rocha, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are descriptive studies that have reported on the extreme degree of ownership concentration that prevailed until recently (Aldrighi & Mazzer, 2005, 2007Leal, Carvalhal-da-Silva, & Valadares, 2002;among others) and the decline in the degree of ownership concentration in Brazilian companies in recent years (Canellas & Leal, 2009;Gorga, 2009;Sternberg, Leal, & Bortolon, 2011), while others have linked ownership structure to performance or market value of a company (Leal & Bortolon, 2009;Leal & Carvalhal-da-Silva, 2006;Okimura, Silveira, & Rocha, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Alguns trabalhos empíricos foram realizados para determinar a estrutura de propriedade e controle das empresas não-financeiras brasileiras, destacando-se Siqueira (1998), Aldrighi e Mazzer Neto (2005e 2007, Gorga (2009) e Cueto (2013). Desses, apenas Gorga (2009) separa as empresas entre os diferentes níveis de governança da BM&FBovespa (mercado tradicional, N1, N2 e NM).…”
Section: Introductionunclassified
“…Os resultados mostram que as famílias e os indivíduos são os principais acionistas das empresas não-financeiras brasileiras. Porém, comparando com os trabalhos de Siqueira (1998), Aldrighi e Mazzer Neto (2005e 2007 e Gorga (2009), observou-se um aumento da participação de investidores institucionais, principalmente dos fundos de investimento, bem como a redução do número de empresas controladas pelo governo. Além disto, houve uma redução da concentração da propriedade e do controle e, ao contrário do observado por esses autores, a maioria das empresas da amostra não possui um acionista controlador.…”
Section: Introductionunclassified
“…O tema deste caso está diretamente ligado à estrutura de propriedade e de controle das organizações e seu comportamento em relação à liquidez de seus papéis negociados em bolsa de valores. Neste aspecto, faz-se necessário entender o significado destes termos que, conforme explicado por Berle e Means (1932 como citado em Aldrighi & Mazzer, 2005), são enunciados como sendo a propriedade pulverizadadividida entre um número grande de acionistase controlecaracterizado pela administração de poucos diretores, os quais são possuidores de um número considerável da fração do capital da companhia, sendo esta fração caracterizada pela propriedade de ações com direito a voto.…”
Section: Análise Do Caso E Revisão De Literaturaunclassified